2021
DOI: 10.1371/journal.pgen.1008919
|View full text |Cite
|
Sign up to set email alerts
|

RAD54 is essential for RAD51-mediated repair of meiotic DSB in Arabidopsis

Abstract: An essential component of the homologous recombination machinery in eukaryotes, the RAD54 protein is a member of the SWI2/SNF2 family of helicases with dsDNA-dependent ATPase, DNA translocase, DNA supercoiling and chromatin remodelling activities. It is a motor protein that translocates along dsDNA and performs multiple functions in homologous recombination. In particular, RAD54 is an essential cofactor for regulating RAD51 activity. It stabilizes the RAD51 nucleofilament, remodels nucleosomes, and stimulates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 108 publications
4
28
0
Order By: Relevance
“…However, homologs of Mek1 and Hed1 have not been identified, nor has the mechanism by which RAD51 is downregulated been described in organisms other than budding yeast. We recently confirmed that Arabidopsis RAD54 is essential for RAD51-mediated recombination and that this includes meiotic DSB repair in dmc1 mutant plants [74] (Figure 8C and E). This study thus further emphasized that the RAD51-RAD54 pathway is down-regulated or plays a minor role in wild-type Arabidopsis meiosis.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, homologs of Mek1 and Hed1 have not been identified, nor has the mechanism by which RAD51 is downregulated been described in organisms other than budding yeast. We recently confirmed that Arabidopsis RAD54 is essential for RAD51-mediated recombination and that this includes meiotic DSB repair in dmc1 mutant plants [74] (Figure 8C and E). This study thus further emphasized that the RAD51-RAD54 pathway is down-regulated or plays a minor role in wild-type Arabidopsis meiosis.…”
Section: Discussionsupporting
confidence: 62%
“…We note however that asymmetric loading has also been previously suggested (in particular in Arabidopsis) and is thus also possible [19]. The nucleofilament is then the active molecular species and data from budding yeast, mouse and Arabidopsis have demonstrated that DMC1 is the active recombinase during meiosis with RAD51 being an essential co-factor for DMC1, but its strand exchange activity being inhibited [21, 3840, 46, 47, 57, 74] (Figure 8A). Thus, absence of RAD51 leads to strong defects in DMC1 loading and therefore defects in meiotic DSB repair [19, 38, 58, 75, 76] (Figure 8B).…”
Section: Discussionmentioning
confidence: 64%
“…Effort has also been made in analyzing the effects of modifying the homology-direct repair (HDR) pathway in plants to improve HR-mediated GT ( Lieberman-Lazarovich and Levy, 2011 ; Pradillo et al, 2014 ; Steinert et al, 2016 ; Hernandez Sanchez-Rebato et al, 2021 ). In yeast, the core components of the HR machinery are RAD51, RAD52, and RAD54 ( Li and Heyer, 2008 ).…”
Section: The Dna Repair Seesaw: Balancing Dna Repair Machineries To E...mentioning
confidence: 99%
“…Another essential cofactor RAD54 regulates RAD51 activity by stabilizing the RAD51 nucleofilament and remodeling of nucleosomes. It also stimulates the homology search and strand invasion activity of RAD51 [ 27 ].…”
Section: The Role Of Polθ In Normal Cellsmentioning
confidence: 99%
“…Following annealing, the ERCC1 (Excision Repair Cross Complementation Group 1) interacts with XPF (Xeroderma Pigmentosum, Complementation Group F), creating a complex that removes the flanking unannealed non-complementary 3′ssDNA. Finally, DNA Ligase I (LIG1) ligates the paired DNA ends [ 27 , 30 ].…”
Section: The Role Of Polθ In Normal Cellsmentioning
confidence: 99%